Anomalous celiac aorta supply to normal basal segments of the lung: a case report - Li, Zhenhua; Wang, Rujuan; Niu, Yiran; Xia, Dongping; Ni, Jixiang (Frontiers in Medicine, 2025)
We present a case of a 28-year-old female patient who has suffered from hemoptysis for a period of 10 years. Examinations revealed an anomalous celiac aorta supply to normal basal segment of the lung. The patient was improved after embolisation with a vascular plug. This case demonstrates the deadly risk posed by anomalous systemic arterial supply to normal basal segments of the lung. As a minimally invasive procedure, transarterial embolization (TAE) is a safe and effective therapeutic choice.